HUBUNGAN TINGKAT PENGETAHUAN TERHADAP PERILAKU DALAM SWAMEDIKASI ANALGETIKA ANAK DI KOTA DENPASAR - Dwidjayanti, Ni Kadek Candra; Suryaningsih, Ni Putu Aryati; Bakta, I Made (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Self-medication is an action taken by society in self-medicating. Knowledge of good medicine is needed in order to determine the appropriate treatment for self-medication. Research on self-medication behavior in the community found that most have good behavior.: This study aims to determine the level of knowledge, and behavior in children's analgetic self-medication. The research design used is quantitative descriptive with a cross-sectional research design. The number of samples used was 100 respondents with probability sampling. Measurements were made using questionnaires with Univariate and Bivariate Test analysis techniques. Percentage of parents' knowledge level in the medium category 40 (40%), parental behavior in the positive category 59 (59%). There was a significant relationship between the level of knowledge and behavior of parents and the p value (0.001). from research on the significant relationship between knowledge and behavior in analgetic self-medication in parents of children in Denpasar City. The need for counseling is more related to children's analgetic self-medication.